A Shotgun Metagenomic Sequencing Exploration of Cabernet Sauvignon Grape Must Reveals Yeast Hydrolytic Enzymes - Ghosh, S.; Divol, B.; Setati, M.E. (South African Journal of Enology and Viticulture, 2021)
Shotgun sequencing was employed to explore the community structure (phylotyping of rRNA genes) and functional potential of Cabernet Sauvignon grape must microbiome. A metagenomic library, representing 92.6 Mb of genetic information, was generated from DNA obtained from Cabernet Sauvignon grape must.. Fungi were identified as the dominant domain (59.5%) followed by Streptophyta (39%). Among the 84 fungal species, 22 were yeasts of various genera. Additionally, grapevine endophytes such as Davidiella sp., Botryotinia fuckeliana, Alternaria sp., and Cladosporium sp. were identified. An unusually high prevalence of Mucor spp. was evidenced. Functional annotation revealed sequences of genes involved in metabolism (35.6%), followed by poorly characterized categories (28.3%), cellular processes and signalling (18.4%), and finally information storage (17.8%). Among the former, glycosidases were abundant followed by glycogen debranching enzyme, 6-phosphofructokinase and trehalose-6-phosphate synthase. Furthermore, the taxonomic analysis of the functional sequence data exhibited the eukaryotic gene pool that predominantly contains sequences derived from Streptophyta (mainly Vitis vinifera) 60% > Ascomycota (32%) > Basidiomycota (5%) > Bacteria (2.5%). Finally, sequences of a variety of hydrolytic enzymes of potential oenological relevance were retrieved, thereby confirming that grape juice is a rich reservoir for valuable biocatalysts that should be explored further.